Análise funcional da proteína 14-3-3 de Paracoccidioides brasiliensis e prospecção de alvos terapêuticos inibidores da interação de P. brasiliensis à pneumócitos - Assato, Patricia Akemi [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Paracoccidioidomycosis (PCM) a systemic mycosis endemic in Latin America, with high prevalence in Brazil, has as etiological agent dimorphic fungi Paracoccidioides spp., P. brasiliensis e P. lutzii. During the infection process the adhesins, substances synthetized by fungi that interacts with host's extracellular matrix (ECM), are important virulence factors for the establishment of infection. A 30kDa protein that belongs to 14-3-3 proteins family stands out in the adhesion process of this fungus. The 14-3-3 proteins are present in all eukaryotic cells and play multiple functions. In P. brasiliensis, the 14-3-3Pb protein binds to lamin, the major component of ECM from host cells, and during the infection the expression is increased. In order to have a better understanding of 14-3-3Pb functions the aim of this study is to perform a functional analysis of this protein through achieving a functional homologous in S. cerevisiae and to analyze the monoclonal antibody anti-14-3-3Pb during infection. S. cerevisiae was chosen as model because it's widely use in genetic research, unlike P. brasiliensis, and has two isoforms of 14-3-3 proteins, Bmh1p and Bmh2p, with high identity with 14-3-3Pb. The functional homologous were obtained by yeast transformation of pYES-14-3-3Pb vector. Complementation assay was performed with obtained transformants, and it was observed that 14-3-3Pb partially complements Bmh1p and Bmh2p, with higher complementation of Bmh2p. Also susceptibility assays were performed with antifungal drugs and semi-synthetic compounds derived from gallic acid where it was observed that S. cerevisiae wild type was less sensitive to antifungals than the knockout strains, S. cerevisiae Δbmh1 and Δbmh2. Monoclonal antibody anti14-3-3Pb was evaluated alone and in association with substances with antifungal activities through inhibition adhesion assay, where it was observed that the anti-14-3-3Pb alone is able to inhibit P. brasiliensis ...

Paracoccidiodomicose (PCM) é uma micose sistêmica endêmica na América Latina, de alta prevalência no Brasil, que tem como agente etiológico os fungos dimórficos do gênero Paracoccidioides, P. brasiliensis e P. lutzii. No processo de infecção as adesinas, substâncias sintetizadas por estes fungos que se ligam a matriz extracelular, são importantes fatores de virulência para o estabelecimento da infecção. A proteína de 30kDa, pertencente a família de proteínas 14-3-3, se destaca no processo adesivo deste fungo. As proteínas 14-3-3 são uma família de proteínas presentes em todas as células eucariotas e possuem múltiplas funções. Em P. brasiliensis, a proteína 14-3-3Pb, liga-se a laminina, principal componente da matriz extracelular das células hospedeiras, e durante a infecção sua expressão é aumentada. Com o intuito de compreender melhor a função desta proteína o objetivo deste estudo foi realizar a análise funcional da 14-3-3Pb através da obtenção de um homólogo funcional em S. cerevisiae e análise do anticorpo monoclonal anti-14-3-3Pb. S. cerevisiae foi escolhida como modelo de estudo por ser uma levedura amplamente utilizada na pesquisa genética, ao contrário de P. brasiliensis, e por possuir duas isoformas de 14-3-3, Bmh1p e Bmh2p, com alta identidade com 14-3-3Pb Para obtenção do homólogo funcional, foi realizada a transformação do vetor pYES-14-3-3Pb em S. cerevisiae. A partir da obtenção dos transformantes a avaliação da complementação foi realizada e foi observado uma complementação parcial das proteínas Bmh1p e Bmh2p por 14-3-3Pb. Ainda foram realizados teste de sensibilidade aos antifúngicos e a derivados semissintéticos do ácido gálico, onde foi possível observar um aumento da sensibilidade das linhagens com nocaute para os genes BMH1 e BMH2, S. cerevisiae Δbmh1 e Δbmh2, quando comparado à linhagem selvagem. A análise do anticorpo monoclonal foi realizada através de ensaio...
Keywords: Paracoccidioidomicose; Micoses fungoides; Paracoccidioides brasiliensis; Mycobacterium tuberculosis; Plasmideos; Mycosis fungoides